Chronic Kidney Disease Patients: Collateral Damage Due to Suspension of Vascular Access Services - Bhatti, Ahsin Manzoor; Arif, Anum; Masud, Mannan; Siddique, Khalid; Saeed, Ali; Khan, Amjad (Pakistan Armed Forces Medical Journal, 2022)
This study was conducted at the Department of Vascular Surgery at Combined Military Hospital Lahore from December 2019to June 2020. The mortality of patients on the waiting list for vascular access in our institution three months afterimplementing strict policies for elective surgeries (30th March 2020 to 29th June 2020) was compared with the preceding threemonths. The mortality of patients in the pre-COVID-19 periods on the waiting list for HD was 11 (7.9%) in the pre-COVID-19 period, while this increased to 5 (12.5%) in the post-COVID-19 period. COVID-19 related suspension of vascular access services negatively influences CKD patients waiting for permanent vascular access.